Legal Measures for Control of Noise Pollution from Mass Rapid Transit - Chantra, Kanyarat (Rajapark Journal, 2024)
This research aimed to 1) study the importance of issues, situations, and the impact of noise pollution from the Mass Rapid Transit system in Thailand; 2) study the basic environmental principles and guidelines from the World Health Organization, government policies, and laws related to prevention and addressing noise pollution from the Mass Rapid Transit systems in England, the United States, and South Korea; 3) study the laws and policies related to preventing and addressing noise pollution from the Mass Rapid Transit system in Thailand; and 4) prepare recommendations, guidelines, and legal measures to prevent and address noise pollution issues from the Mass Rapid Transit within the context of Thai society. This research project is qualitatively based on documentary analysis with data collection, textbooks, related articles, and electronic information from domestic and international sources. The research findings indicate that Thailand’s laws currently lack specific provisions for controlling noise pollution from Mass Rapid Transit and the existing provisions that could potentially be applied to such cases are inadequate. The researcher therefore proposes policy recommendations to expedite the completion of the 15-year Master Plan for Noise and Vibration Pollution Management (2023 – 2037) by the Pollution Control Department. Enhance policies to increase the number of specialized personnel in controlling noise pollution from mass rapid transit and allocate additional funding for controlling noise pollution from mass rapid transit. Legal Recommendations: In the short term, propose the enactment of secondary legislation to establish noise standards and methodologies for measuring noise levels from mass rapid transit. Advocate for designating "Mass Rapid Transit" as a pollution source requiring regulation under Section 68 of the Enhancement and Conservation of National Environmental Quality Act, B.E. 2535. In the long term, propose the drafting of ‘the Noise Pollution Control Act B.E. ...,’ a new legislation specifically addressing all aspects of noise pollution control and defining a category specifically for regulating noise pollution from mass rapid transit.